City-level emergy metabolism accounts for China’s 281 cities from 2000 to 2020 - Miaohan Tang; Gengyuan Liu; Jingke Hong; Weier Liu; Chao Zhong; Dan Wang; Yuli Shan (Scientific Data)
Abstract Cities exhibit diverse urban metabolism patterns in terms of the natural environment, industrial composition, energy, and material consumption. A chronicled city-level quantification of emergy metabolic flows over time can significantly enhance the understanding of the temporal dynamics and urban metabolism patterns, which provides critical insights for the transitions to sustainability. However, there exists no city-level urban emergy metabolism dataset in China that can support detailed spatial-temporal analysis. In this study, we present a city-level urban emergy metabolism dataset of China’s 281 cities between 2000 and 2020. This dataset meticulously describes the production and import of 41 resource types that sustain metabolic activities in 281 Chinese cities over a span of 21 years. This database, for the first time, provides insights into the historical metabolic changes of China’s cities by detailing emergy flows including production, consumption, and import of resources. Furthermore, these emergy flow inventories serve as valuable resources for studying urban metabolic characteristics, evaluating policy impacts, and formulating sustainable development strategies for China’s cities.